The first three years of screening for medium chain acyl-CoA dehydrogenase deficiency (MCADD) by newborn screening ontario - Fisher Lawrence; Wilson Kumanan; Potter Beth K; Kennedy Shelley; Geraghty Michael; Milburn Jennifer; Chakraborty Pranesh (BMC, 2010)
Abstract Background Medium chain acyl-CoA dehydrogenase deficiency (MCADD) is a disorder of mitochondrial fatty acid oxidation and is one of the most common inborn errors of metabolism. Identification of MCADD via newborn screening permits the introduction of interventions that can significantly reduce associated morbidity and mortality. This study reports on the first three years of newborn screening for MCADD in Ontario, Canada. Methods Newborn Screening Ontario began screening for MCADD in April 2006, by quantification of acylcarnitines (primarily octanoylcarnitine, C8) in dried blood spots using tandem mass spectrometry. Babies with positive screening results were referred to physicians at one of five regional Newborn Screening Treatment Centres, who were responsible for diagnostic evaluation and follow-up care. Results From April 2006 through March 2009, approximately 439 000 infants were screened for MCADD in Ontario. Seventy-four infants screened positive, with a median C8 level of 0.68 uM (range 0.33-30.41 uM). Thirty-one of the screen positive infants have been confirmed to have MCADD, while 36 have been confirmed to be unaffected. Screening C8 levels were higher among infants with MCADD (median 8.93 uM) compared to those with false positive results (median 0.47 uM). Molecular testing was available for 29 confirmed cases of MCADD, 15 of whom were homozygous for the common c.985A > G mutation. Infants homozygous for the common mutation tended to have higher C8 levels (median 12.13 uM) relative to compound heterozygotes for c.985A > G and a second detectable mutation (median 2.01 uM). Eight confirmed mutation carriers were identified among infants in the false positive group. The positive predictive value of a screen positive for MCADD was 46%. The estimated birth prevalence of MCADD in Ontario is approximately 1 in 14 000. Conclusions The birth prevalence of MCADD and positive predictive value of the screening test were similar to those identified by other newborn screening programs internationally. We observed some evidence of correlation between genotype and biochemical phenotype (C8 levels), and between C8 screening levels and eventual diagnosis. Current research priorities include further examining the relationships among genotype, biochemical phenotype, and clinical phenotype, with the ultimate goal of improving clinical risk prediction in order to provide tailored disease management advice and genetic counselling to families.